The Impact of Supervised Exercise Training on Traditional Cardiovascular Risk Factors in Patients With Intermittent Claudication: A Systematic Review and Meta-Analysis. (July 2019) - Cornelis, Nils; Nassen, Julie; Buys, Roselien; Fourneau, Inge; Cornelissen, Véronique
Abstract : Background: Patients with intermittent claudication (IC) are at increased risk of cardiovascular (CV) morbidity and mortality. Whereas extensive evidence supports the beneficial effects of supervised exercise training (SET) on walking capacity, little is known about the effect of SET on the CV risk profile of IC patients. Therefore, the aim was to evaluate the effects of SET on CV risk factors in IC patients by using meta-analysis techniques. Methods: A systematic search in the electronic databases MEDLINE, EMBASE, CINAHL, and CENTRAL was conducted from the earliest date available until October 2, 2018. Randomised and non-randomised controlled trials lasting ≥ four weeks and investigating the effect of SET on CV risk factors in IC patients were included. Traditional CV risk factors were studied as primary outcomes; pain free walking distance (PFWD) and maximum walking distance (MWD) were included as secondary outcomes. Data were pooled using random effects models with summary data reported as weighted means and 95% confidence interval (CIs). Results: Fifteen trials were included, involving 18 study groups (nine walking, four resistance, two aerobic training, and three combined groups), totalling 725 patients (mean age 66.3 years; mean ankle brachial index, 0.64). Exercise reduced systolic blood pressure (−5.8 mmHg; CI –9.89 to 1.67, p  < .01) whereas all other CV risk factors (i.e., body weight, body mass index, diastolic blood pressure, and blood lipids) remained statistically unaltered. Exercise also improved PFWD (+132 m; CI 70–194, p  < .001) and MWD (+183 m; CI 98–268, p  < .001). Conclusion: This meta-analysis supports the beneficial effects of SET on walking capacity. Little evidence for an improvement of the CV risk profile was found following exercise in patients with IC. However, given the scarcity of data, high quality RCTs that include an assessment of CV risk factors are urgently required to determine the effect of exercise therapy in the secondary prevention of CV disease of IC patients.